A Bodily Code Analysis Used in Revealing an Imaginary Character in Calvin and Hobbes - Dimas Setiawan (Passage, 2013)
The study entitled “A Bodily Codes Analysis Used in Revealing an Imaginary Friend Character in Bill Watterson’s Comic Strip: Calvin and Hobbes” seeks to discover the representation of imaginary character of Hobbes based on his bodily codes occurred in the 5 selected strips purposively. To obtain deeper understanding, this study applies four basic premises of experientialism proposed by Buckland (2004) towards 9 bodily codes proposed by Chandler (2002). This study uses a qualitative method in order to describe the premises in a narrative way. It discovered that Hobbes makes 76 bodily codes. There are 14 appearances as a real tiger (18.42%), 14 gestures (18.42%), 12 postures (15.79%), 9 proximities (11.84%), 9 physical orientations (11.84%), 8 facial expressions (10.53%), 7 gazes (9.21%), 3 bodily contacts (3.95%), and 0 head-nods (0%). Furthermore, this study also discovered 5 representations of Hobbes. The first is Hobbes as a cloning of Calvin. The second representation is Hobbes as a friend of Calvin. Third, Hobbes is represented as a pet. The forth representation is Hobbes as an opponent of Calvin. Lastly, Hobbes is represented as a real tiger which has instincts as a wild animal. Therefore, in Bill Watterson’s Calvin and Hobbes, Hobbes is visualized as something very close to very distant for Calvin. Keywords: Bodily Codes, Basic Premises of Experientialism, Representation, Comic Strip.